ANALISIS PENGARUH NILAI PELANGGAN DAN LOKASI TERHADAP MINAT TERUS SEBAGAI PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA KOST SEKITAR TEMBALANG DALAM EMPAT WILAYAH - Fauzan, Fajar; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2015)
This research was motivated by the phenomenon of the emergence of consumer dissatisfaction shown by customer canâ€™t settled in the long time in kostan around Tembalang on four regions. this research is directed to analyze on how to customer value, place and customer satisfaction can be affect interest continue as customer in kostan around Tembalang on four regions.This research was conducted in kostan around Tembalang in four regions, the object of study is consumers in kostan around tembalang on four regions. This study aims to detemine the effectÂ Consumer value, Plac on interest continue as Customer with customer satisfaction as variable intervening in kostan around Tembalang on four regions. I In this study data were collected with a questionnaire to 100 respondents (occupants) and the techniques used are non-probability sampling technique with Accidental Sampling approach which aims to determine the responses to each variable n this research The data that meet the test validity, test reliability and test classic assumptions that form a regression equation and Sobel test.Based on t test, most influential first customer satisfaction to results obtained in the form of the coefficient values of 3.414 and a significance of 0.001 can therefore be said that the customers satisfaction and a significant positive effect on interest continue as customer. The second effect is the customer value with the results obtained in the form of the coefficient values of 3,056 and 0.003 for significance can therefore be said that the customer value has a positive effect on interset continue effect and significance. The third effect is obtained with the placeÂ resulted in a coefficient of 2.867 and 0.005 for significance can therefore be said that the positive place and the significance interest continue as customer. From the analysis using the regression can be seen that the variables costumers value, place, and customer satisfaction are all positive and significant effect on interest continue as customer in kostan around Tembalang on four regions.